Biochemical and physiological response of passion fruit during the process of healing after two methods of grafting - Takata, W. H.S. [UNESP]; Vieira, M. C.S. [UNESP]; Macedo, A. C. [UNESP]; Lima, G. P.P. [UNESP]; Ono, E. O. [UNESP]; Narita, N. (International Society for Horticultural Science (ISHS), 2016)
The cultivation of passion fruit in Brazil is impaired due to the high level of infection by soil pathogens that cause premature death. The use of grafting is very promising, using Passiflora giberti as a rootstock and Passiflora edulis f. flavicarpa as a scion. However, the yield is lower than non-grafted plants. By this reason, the use of grafting and maintenance of the two roots are presenting good results, so, this work aimed to study the influence of the two grafting methods on antioxidant enzymes and gas exchange during the healing after grafting. This study was conducted in a greenhouse with seedlings of Passiflora giberti and P. edulis f. flavicarpa. The graft was made two months after germination, and the superoxide was evaluated, as well as catalase, polyphenol oxidase and peroxidase activity in the graft site every three days starting one day after grafting. Gas exchange analysis was made every two days evaluating the CO2 assimilation, stomatal conductance, intracellular content of CO2 and transpiration. The results showed that the grafted plants with maintenance of two roots presented very similar enzyme activity to the non-grafted plants even as to the gas exchange analysis. On the other hand the traditional graft method presented high levels of enzymes activity whilst CO2 assimilation, stomatal conductance and transpiration was lower until the seventh day, when it began to increase, equating to the other treatments at 13 days after grafting. According to the results, the conventional method of grafting appears to be more stressful, demanding a longer period of recovery.
Keywords: Enzymes; Passiflora edulis; Passiflora giberti; Photosynthesis; Two root systems